Is an obesity simulation suit in an undergraduate medical communication class a valuable teaching tool? A cross-sectional proof of concept study. Issue 8 (5th August 2019) - Herrmann-Werner, Anne; Loda, Teresa; Wiesner, Lisa M; Erschens, Rebecca Sarah; Junne, Florian; Zipfel, Stephan
Abstract : Objective: With the growing prevalence of overweight and obesity, medical students should be prepared to engage in weight management and obesity-related communications in order to prevent patients from having stigmatising experiences. In addition, medical students should have training to reduce anti-fat prejudices. Design: Cross-sectional proof of concept study. Setting: University Hospital Tuebingen, Germany. Participants: 246 participants (207 second-year medical students, 13 standardised patients (SPs) and 22 teachers) took part in the study. Primary and secondary outcome measures: The primary outcome was the assessment of degree of reality of the encounter with the SP wearing an obesity simulation suit (OSS). The secondary outcome was the evaluation of students' awareness and prejudice against patients with obesity in a simulated role play. Additionally, a description of the advantages and disadvantages when using such a teaching tool is delivered. Results: The OSS contributed to a realistic perception of the patient group depicted in a role play according to students, teachers and SPs. OSS body mass index estimation by students, teachers and SPs correctly was over 30 kg/m 2 —thus in the range of obesity. In a selected subscale of the Anti-Fat Attitudes Test, students showed significantly stronger anti-fat stigmatisation compared with teachers and SPs. Conclusions: An OSS worn by an SP is a valuable teaching tool to raise awareness about patients with obesity. It gives a realistic picture of the encounter. Stigmatisation was low in general but was especially present in the students. Further research should include intervention studies to address this issue.